Association of Methylenetetrahydrofolate Reductase rs1801133 Genetic Variants with Type 2 Diabetes Mellitus and Diabetic Nephropathy - Bayramoglu, Aysegul; Bayramoglu, Gokhan; Guler, Halil Ibrahım; Coban, Nezaket; Korkmaz, Mustafa Çagatay (Makara Journal of Health Research, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a complex metabolic disease with a genetic predisposition. Methylenetetrahydrofolatereductase (MTHFR) gene is one of the candidate genes associated with T2DM and diabetic nephropathy (DN). This research was carried out to determine the frequency of the C677T polymorphism (rs1801133) of the MTHFR gene and examine the role of rs1801133 polymorphism in T2DM and DN development. Methods: DNA was obtained from peripheral blood samples (273 samples) using a DNA isolation kit. MTHFR rs1801133 polymorphism was determined using polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP), and electrophoresis. PCR products were cut by restriction enzyme HiNF I and analyzed by 2% agarose gel electrophoresis. The results were statistically analyzed. Results: Although MTHFR rs1801133 genotype frequencies showed statistically significant differences between the control and T2DM patient groups (p = 0.001), no statistically significant difference was found between individuals with and without DN. Conclusions: MTHFR gene rs1801133 polymorphism is related to T2DM but not to DN. CT and TT genotypes can be accepted as genetic markers.